FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN PENGENDALIAN HAMA TERPADU (PHT) PADA TANAMAN SAYURAN KABUPATEN AGAM, SUMATERA BARAT - Sari, Nila (Fakultas Pertanian Universitas Mataram, 2025)
Integrated pest management (IPM) is a planned and coordinated effort for sustainable and environmentally sound agricultural development so that pests and diseases remain at the threshold and production continues to increase. The purpose of this paper is to analyze the factors that influence the application of IPM. The research was conducted in Kenagarian Koto Tinggi, Agam Regency. The number of research samples was 90 farmers who were determined using the Slovin formula. Field research began in April to May 2022. Primary data were collected through questionnaires, in-depth interviews and observations for farmer characteristics variables including age, formal education, length of farming, land area owned, family dependents, status in farmer groups and farmer motivation towards IPM. IPM. Furthermore, the research variables also include perceptions of IPM extension variables, the role of extension agents, environmental support and the nature of innovation. Data processing is done descriptively and to see the factors that influence the application of IPM with multiple linear regression test by previously transforming ordinal data into intervall data. The results of multiple linear regression test showed that the factors that significantly affect the application of IPM by farmers are the length of farming, farmer motivation, the role of extension workers as facilitators and motivators, the availability of production facilities and market opportunities as well as relative advantage and easy to observe.